The best of both worlds? Use of Kaizen and other continuous improvement methodologies within Portuguese ISO 9001 certified organizations - Fonseca, Luís Miguel (2018)
Purpose – ISO 9001:2015 edition, by adopting modern management and quality approaches, can foster the application of continuous improvement (CI) methodologies. The purpose of this paper is to assess the level of utilization of Kaizen and other CI methodologies within Portuguese ISO 9001 certified organizations, namely, amid organizations that have already implemented ISO 9001:2015. Design/methodology/approach – After the literature review, a quantitative research, supported on an online survey, was adopted. The survey yielded 309 valid responses (response rate 18 percent) encompassing 71 organizations already certified against ISO 9001:2015 and the remaining 238 against ISO 9001:2008. The results of the statistical analysis performed were reviewed with a focus group of five quality and organizational excellence managers. Findings – The results show a mildly use of Kaizen, Lean and Six Sigma (SS) by Portuguese ISO 9001 certified organizations, which is increase when compared to previous studies. The sample of organizations that are already certified by ISO 9001:2015 have mean and median levels of customer improvement methodologies adoption (Lean, Kaizen, SS) higher than those that are still certified against ISO 9001:2008. However, the Kruskal-Wallis test showed that these differences are not statistically significant. Concerning the adoption of these methodologies by activity sector, the sample median values seem to suggest that Lean and SS are more commonly adopted in the industry than in the services, but according to the Kruskal-Wallis test these differences are not statistically significant. Checklists, plan-do-check-act cycle and process diagrams, followed by DMAIC, are the quality tools that are most frequently adopted. A high workload due to the transition process for ISO 9001:2015 and the lack of qualified people were suggested as possible explanations for these results by the Expert Focus Group. Research limitations/implications – The study is restricted to ISO 9001 certified organizations in Portugal and due to the short time since ISO 9001:2015 implementation it should be considered as having an explanatory nature and subject to future confirmation. Originality/value – This study on the application of CI methodologies between ISO 9001:2015 and ISO 9001:2008 certified organizations contributes to the Kaizen and CI body of knowledge and provides inputs to the organizations and professionals that aim to successfully apply it.